Synthesis of Fluorocyclotriphosphazene Derivatives and Their Fire-Retardant Finishing on Cotton Fabrics - Li Zhanxiong; Du Liping (International Journal of Polymer Science)
A series of novel fire-retardant agents, fluorocyclotriphosphazene derivatives with the substitution groups of 2,2,3,3-tetrafluoropropoxy groups were synthesized using hexachlorocyclotriphosphazene and 2,2,3,3-tetrafluoropropyl alcohol as starting materials. The synthesized fire-retardant agent was emulsified and applied on the cotton fabric finishing to reduce the flammability and afford water/oil repellency simultaneously. The optimum finishing process was achieved according to the test of cotton finishing with fluorocyclotriphosphazene. The treated cotton showed not only excellent fire-retardant performance, but also water and oil repellency with little change in strength and whiteness.